Spatial/Temporal Characterization and Risk Assessment of Trace Metals in Mangla Reservoir, Pakistan - Muhammad Saleem; Javed Iqbal; Gulraiz Akhter; Munir H. Shah (Journal of Chemistry)
Composite water samples were collected from different sites of Mangla reservoir, Pakistan, in premonsoon, monsoon, and postmonsoon seasons. The physicochemical parameters and trace/heavy metals were determined in all water samples. The results manifested significant seasonal variations among Co, Cr, Ni, and Pb and the metals exhibited highest contribution in premonsoon season except Mn. Principal component analysis (PCA) and cluster analysis (CA) revealed considerable anthropogenic intrusions in the reservoir. Probable risk associated with the metals levels on human health was also evaluated using hazard quotients (HQ) by ingestion and dermal routes for adults and children. It was noted that Cd, Co, Cr, Ni, and Pb (HQing>1) were the most important pollutants leading to noncarcinogenic concerns. The HQderm levels of all metals were below unity, suggesting that these metals posed no hazards via dermal absorption, while the oral intake was the major exposure pathway. The largest contributors to chronic risks were Cd, Co, Cr, Ni, and Pb in all the seasons. Therefore, immediate measures should be taken for sustaining the healthy aquatic ecosystem.